Addictive use of smartphone, depression and anxiety among female undergraduates in Nigeria: a cross-sectional study - Olusola Ayandele; Olugbenga A Popoola; Tolulope O Oladiji (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - This study examined the prevalence and relationship between addictive use of smartphones and symptoms of depression and anxiety among female undergraduates. Design/methodology/approach - Standardized scales were used to measure the addictive use of smartphones, depression and anxiety among 398 female students (mean age 21.75 years, SD = 2.67) at two large higher institutions in southwest Nigeria and were opportunely sampled. Two hypotheses were tested using Spearman's rho and Mann-Whitney U tests. Findings - The results showed that 1.01% of the respondents were probable smartphone addicts and 17.34% were at-risk, while 14.32% and 16.33% manifested symptoms of anxiety and moderate-to-severe depression, respectively. Depression (r = 0.24, p < 0.01) and anxiety (r = 0.21, p < 0.01) have significant relationship with addictive use of smartphone. Addictive/at-risk smartphone users significantly scored higher on symptoms of depression (average rank of 233.40) than normal smartphone users (average rank of 191.88); U = 9387.50; z = −2.81, p < 0.05; Also, addictive/at-risk smartphone users reported significantly higher level of anxiety (average rank of 229.27) than normal smartphone users (average rank of 192.81); U = 9689.00; z = −2.46, p < 0.05. Research limitations/implications - Generalizing these results to a clinical setting and other at-risk demographic groups might prove difficult due to the respondents' condition of homogeneity. Practical implications - The findings suggest that relationships exist between the addictive use of smartphones and symptoms of depression and anxiety among undergraduate students in southwest Nigeria. Clinicians should assess smartphone use in the management of depression and anxiety disorders. Social implications - University administrators should target prevention and intervention strategies that would assist students to be taught positive ways of using their smartphones. Originality/value - The study contributes to the body of knowledge by revealing relationships between smartphone addiction and mental health in an African sample.